2015
DOI: 10.1111/1365-2435.12455
|View full text |Cite
|
Sign up to set email alerts
|

Variation of xylem vessel diameters across a climate gradient: insight from a reciprocal transplant experiment with a widespread boreal tree

Abstract: 1. Xylem vessel diameters represent an important plant hydraulic trait to ensure sufficient water supply from the roots to the leaves. The ability to adjust the hydraulic pathway to environmental cues is key in order to satisfy transpirational demands and maximize growth and survival. 2. We evaluated the variability of vessel diameters in trembling aspen in a reciprocal transplant experiment. We tested six provenances from three ecological regions of North America planted at four test sites in western Canada. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 69 publications
4
55
1
Order By: Relevance
“…First, P × E may affect among‐population phenotypic differences across environments. For instance, Schreiber, Hacke, Hamann, & Baltzer (), in a study on trembling aspen ( Populus tremuloides ), found that among‐population variation in vessel diameter was observed only in the southernmost gardens, whereas populations showed similar vessel diameters in the northern, boreal sites. Second, P × E may also alter the relationship of mean traits with geographical and/or climatic variables at the population sources that are commonly used as evidence of local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…First, P × E may affect among‐population phenotypic differences across environments. For instance, Schreiber, Hacke, Hamann, & Baltzer (), in a study on trembling aspen ( Populus tremuloides ), found that among‐population variation in vessel diameter was observed only in the southernmost gardens, whereas populations showed similar vessel diameters in the northern, boreal sites. Second, P × E may also alter the relationship of mean traits with geographical and/or climatic variables at the population sources that are commonly used as evidence of local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been a focus on species mean trait values; however, for species to be able to adapt to climate change they require, heritable, intraspecific trait variation. Yet, a few studies focus on intraspecific trait variation and if these traits are genetically determined (e.g., Aranda et al, ; Schreiber, Hacke, & Hamann, ; Hajek, Kurjak, von WĂŒhlisch, Delzon, & Schuldt,; Madani et al, ). There is growing appreciation of the importance of intraspecific variation in functional and complex traits in providing the capacity to adapt to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…At the current atmosphere [CO 2 ], xylem anatomy showed a significant response to water deficit in maize stems, with decreases in vessel diameter ( D c ), vessel roundness ( R c ), and stem cross‐section area ( A stem ; Table ). Studies of many trees and crops report similar long‐term response to water stress (Arend & Fromm, ; Awad et al, ; Hudson et al, ; PlavcovĂĄ & Hacke, ; Schreiber et al, ; Stiller, ). Photosynthetic capacity is associated with xylem formation because assimilation is crucial not only for the synthesis of cell wall products but also for maintaining turgor pressure in the enlarging cells (Larcher, ; Ray, Green, & Cleland, ; Steppe et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Soil drying is the most frequent and primary environmental stress that plants face. Experiments conducted under natural conditions across climatic and environmental gradients indicate that xylem conduit diameter, conduit length, hydraulic conductivity, and vulnerability to embolism of tree branches were positively correlated with local precipitation or soil water availability (Choat et al, ; Schreiber, Hacke, Hamann, & Baltzer, ; Villar‐Salvador, Castro‐DĂ­ez, PĂ©rez‐RontomĂ©, & Montserrat‐MartĂ­, ). Similar findings have been recorded in experiments under controlled environment conditions.…”
Section: Introductionmentioning
confidence: 99%